P192 LONG TERM PROGNOSTIC EFFECT OF LIPROTEIN(A) IN PATIENTS WITH AND WITHOUT DIABETES MELLITUS AFTER MYOCARDIAL INFARCTION. (18th May 2022) - Cancro, F; Baldi, C; Silverio, A; Di Maio, M; Esposito, L; Tedeschi, M; Cristiano, M; Sabatino, M; Romei, S; Vecchione, C; Galasso, G
Abstract: Aims: To describe the baseline clinical, laboratory and angiographic characteristics of patients with acute myocardial infarction (MI) according to the presence or not of diabetes mellitus (DM), and to evaluate if DM may influence the effect of lipoprotein(a) [Lp(a)] serum level on long–term outcome in this very high–risk population. Methods: This was a retrospective, single–center, study including consecutive patients admitted with MI diagnosis between January 1, 2017, and December 31, 2020. The availability of data on baseline Lp(a) serum level was considered as an inclusion criterion. The study population was divided into two groups according to the presence or not of DM. The Lp(a) value of 50 mg/dL was used to test the hypothesis of a different effect of Lp(a) on the clinical outcome of patients with or without DM. The primary study outcome was all–cause death at 3–year follow–up. Results: The study population included 997 patients (mean age 63.7±13.5 years; 75.7% were males). Diabetes was reported in 280 (28.1%) patients. DM patients were older than those without DM (67.8±12.1 vs. 62.0±13.7 years, p < 0.001) and showed a significantly higher prevalence of dyslipidemia, hypertension, obesity, prior MI and prior coronary revascularization (p < 0.001). DM patients showed higher SYNTAX score value (19.8 vs. 15.1, p < 0.001) and a higher prevalence of left main involvement (6.3 vs. 3.1, p = 0.023). At Kaplan–Meier analysis, in the group without DM, patients with Lp(a)≥50 mg/dL showed a significantly lower long–term survival compared with those with Lp(a)<50 mg/dL (Log–Rank=0.004). In DM patients DM, conversely, no survival difference was found between patients with Lp(a)≥50 mg/dL vs. those with Lp(a)<50 mg/dL. At multivariable Cox regression analysis, in patients without DM, Lp(a) serum level (HR: 2.68, 95% CI 1.23–5.83; p = 0.013) and age (HR: 1.06, 95% CI 1.04–1.09; p < 0.001) were independent predictors of mortality at 3–year follow–up. Among DM patients, only age was independently associated with 3–year mortality (HR: 1.07, 95% CI 1.03–1.10; p < 0.001) (Table). Conclusion: In this MI population, Lp(a) was independently associated with long–term mortality in patients without DM, but not in patients with DM. Whether DM can modify the effect of Lp(a) on clinical outcome after MI requires confirmation by larger prospective studies.